2018
DOI: 10.1007/978-981-13-3582-2_12
|View full text |Cite
|
Sign up to set email alerts
|

“Senator, We Sell Ads”: Analysis of the 2016 Russian Facebook Ads Campaign

Abstract: One of the key aspects of the United States democracy is free and fair elections that allow for a peaceful transfer of power from one President to the next. The 2016 US presidential election stands out due to suspected foreign influence before, during, and after the election. A significant portion of that suspected influence was carried out via social media. In this paper, we look specifically at 3,500 Facebook ads allegedly purchased by the Russian government. These ads were released on May 10, 2018 by the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
0
27
0
3
Order By: Relevance
“…VADER is unique in using the sentiment of particular words as well as accounting for word-order relationships and particularities of abbreviations. This is an extensively validated tool for social media analysis and generates some of the most accurate classifications in a benchmark of sentiment analysis tools (20)(21)(22). Our validation of the VADER sentiment scores in our dataset was done by sampling posts from the bottom, median, and top 10% of VADER scores and having student coders hand-label the tone.…”
Section: Methodsmentioning
confidence: 99%
“…VADER is unique in using the sentiment of particular words as well as accounting for word-order relationships and particularities of abbreviations. This is an extensively validated tool for social media analysis and generates some of the most accurate classifications in a benchmark of sentiment analysis tools (20)(21)(22). Our validation of the VADER sentiment scores in our dataset was done by sampling posts from the bottom, median, and top 10% of VADER scores and having student coders hand-label the tone.…”
Section: Methodsmentioning
confidence: 99%
“…Especially for the spread of fake news, various studies showed how political leaning [1], age [28], and education [49] can greatly affect fake news spread, alongside with other mechanisms that leverage emotions [20,21] and cognitive limits [44,45]. Additionally, Dutt et al [16] showed how foreign actors can more so than just backing one candidate or the other, often manipulate social media for the purpose of sowing discord.…”
Section: Political Manipulationmentioning
confidence: 99%
“…Efforts, spearheaded by the Russian Internet Research Agency (IRA) and others, to deliberately manipulate social media discourse have been well documented both in the 2016 U.S. presidential election (Bessi et al, 2016) and the 2017 French presidential election (Ferrara, 2017). The IRA appeared to have identified and targeted non-white voters (Badawy et al, 2019) months before the election with messages promoting racial identity (Dutt et al, 2018) that may have led to voter suppression (Kim et al, 2018), and certainly sowed division and conflict online (DiResta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%